PENGARUH PENGHARGAAN, KEPERCAYAAN DAN PEMBERDAYAAN TERHADAP KOMITMEN PERAWAT RUMAH SAKIT ERIA BUNDA PEKANBARU - B Nahor Christiani Ananda; Machasin Machasin; pramadewi Arwinence (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This research was conducted at Eria Bunda Hospital Pekanbaru. Thisstudy aims to determine the effect of reward, trust and empowerment on thecommitment of nurses at Eria Bunda Hospital Pekanbaru. The population in thisstudy included all nurses at Eria Bunda Hospital Pekanbaru, totaling 73 people.The primary data was collected through a questionnaire as an instrument to provethe result of the study. The sampling technique in this study is a saturatedsampling technique (census) which means making all member of the population asa sample. Data analysis used multiple linear regression analysis method withSPSS version 23 program. The results showed that : 1) reward had a positive andsignificant effect on nurses commitment at Eria Bunda Hospital, 2) trust had apositive and significant effect on nurses commitmentat Eria Bunda Hospital, 2)Empowerment had a positive and significant effect on nurses commitment EriaBunda Hospital, 4) reward, trust and empowerment had a positive and significanteffect on the commitment of nurses at Eria Bunda Hospital Pekanbaru. Keywords : Reward, Trust, Empowerment, commitment